2014
DOI: 10.1055/s-0034-1369807
|View full text |Cite
|
Sign up to set email alerts
|

A New Plane of Elevation: The Superficial Fascial Plane for Perforator Flap Elevation

Abstract: Background?The aim for microsurgical reconstruction has broadened from achieving functional to also providing good esthetic outcomes. The perforator flaps are widely used for this goal. However, perforator flaps can still be bulky especially to resurface the skin defect. We hypothesized that elevation from the superficial fascial plane can obtain a thin and viable flap. Method?In this retrospective study, we report consecutive perforator flaps elevated at the superficial fascial plane from November 2007 to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(68 citation statements)
references
References 20 publications
(28 reference statements)
2
58
0
1
Order By: Relevance
“…Selection of optimal flap type was based on the size and depth of the defect, the length of the pedicle, and patient posture during surgery. Flap elevation was performed according to the protocol of our institution [11][12][13]. The flaps used in the present study were anterolateral thigh flap, superficial circumflex iliac artery perforator flap, superior gluteal artery perforator flap, radial free forearm flap, posterior interosseous flap, and gracilis muscle flap.…”
Section: Surgical Protocolmentioning
confidence: 99%
“…Selection of optimal flap type was based on the size and depth of the defect, the length of the pedicle, and patient posture during surgery. Flap elevation was performed according to the protocol of our institution [11][12][13]. The flaps used in the present study were anterolateral thigh flap, superficial circumflex iliac artery perforator flap, superior gluteal artery perforator flap, radial free forearm flap, posterior interosseous flap, and gracilis muscle flap.…”
Section: Surgical Protocolmentioning
confidence: 99%
“…Suprascarpa's harvest of perforator flaps is an established technique [9,10]. Although it has -to the best of our knowledge -never been reported for a DIEAP flap before, we find it even easier than a TDAP, ALT or SGAP since the vertical fibrous septa are looser and less numerous, the lobules larger and the perforators constantly of large calibre, thus easy to visualize.…”
Section: Discussionmentioning
confidence: 80%
“…Originalarbeit eral authors, and the same holds true for thin flaps [9,10,[12][13][14][15][16][17]. Thus this is just another application of a well established technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, unresolved edema with inherent fibrosis created a bulky appearance. In a larger series, Hong et al [23] reported that six of 282 thin perforator flaps harvested at the superficial fascial plane required secondary debulking procedures.…”
Section: Discussionmentioning
confidence: 99%